2024
DOI: 10.1088/1361-6668/ad2300
|View full text |Cite
|
Sign up to set email alerts
|

Study of the demagnetization behavior of no-insulation persistent-current mode HTS coils under external AC fields by 3D FEM simulation

Zhuoyan Zhong,
Wei Wu,
Guangtong Ma
et al.

Abstract: The no-insulation (NI) winding technique is promising to be applied in the persistent-current mode (PCM) operation of high-temperature superconducting (HTS) coils to provide those advantages. To apply the NI PCM coil, its demagnetization behaviour (i.e., decay of persistent DC current) by external AC field, which occurs in maglev trains, electric machines, and other dynamic magnet systems, is essential to be understood. For this purpose, a 3D FEM model, capturing the full electromagnetic properties of NI HTS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 119 publications
(155 reference statements)
0
0
0
Order By: Relevance
“…Recently, modeling of NI coil based on FEM technique has attracted much more attention. As reported in [32,33], The NI coil can be modeled as an anisotropic resistivity bulk to take into account the contact resistivity:…”
Section: Appendix Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, modeling of NI coil based on FEM technique has attracted much more attention. As reported in [32,33], The NI coil can be modeled as an anisotropic resistivity bulk to take into account the contact resistivity:…”
Section: Appendix Bmentioning
confidence: 99%
“…It can be found that the radial resistivity ρ n is several orders of magnitude different from the tangential resistivity ρ t , which poses challenges for the numerical modeling of NI coil. In literature [33], the second order curl elements are employed to discretize Maxwell's equations, which provides delicate modeling of the anisotropic resistivity model. A case study of NI coils is given and detailed parameters have been introduced in section 3.…”
Section: Appendix Bmentioning
confidence: 99%
See 1 more Smart Citation